The Management Accounting Practices in Albania in the Context of Globalization - Manjola Naco; Hysen Cela; Petrit Dollani (Contemporary Economics)
The main aim of the paper is to provide relevant findings on the status of management accounting in Albanian Accounting Practices, based on the direct survey with selected companies and individuals (experts on the field). In our analysis we have used as a benchmark the IFAC statement on Management Accounting Concepts and its description of the evolution of management accounting. To achieve our objectives we prepared and provided to a large group of professional accountants (that mainly are dealing with bookkeeping and financial statement preparations) a structured questionnaire, containing several questions on the status of the practices applied in Albania on management accounting. This survey was carried out during the first half of 2009. Findings of this paper are based on the answers given by 300 respondents. These answers point out that management accounting practices in Albania tend not to be complex and sophisticated. Budgeting, product profitability and financial performance measurement remain the central pillars, while other, most contemporary, management accounting techniques are sporadically used. There is also little evidence of management accounting concerned directly with "value creation".